1992
DOI: 10.1093/nar/20.7.1691
|View full text |Cite
|
Sign up to set email alerts
|

Strand displacement amplification—an isothermal,in vitroDNA amplification technique

Abstract: Strand Displacement Amplification (SDA) is an isothermal, in vitro nucleic acid amplification technique based upon the ability of HincII to nick the unmodified strand of a hemiphosphorothioate form of its recognition site, and the ability of exonuclease deficient klenow (exo- klenow) to extend the 3'-end at the nick and displace the downstream DNA strand. Exponential amplification results from coupling sense and antisense reactions in which strands displaced from a sense reaction serve as target for an antisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
415
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 764 publications
(420 citation statements)
references
References 6 publications
0
415
0
5
Order By: Relevance
“…In addition to the widely used PCR-based detection (1,2), several amplification methods have been invented. They include nucleic acid sequence-based amplification (NASBA) (3), self-sustained sequence replication (3SR) (4) and strand displacement amplification (SDA) (5,6). Each of these amplification methods has its own innovation to re-initiate new rounds of DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the widely used PCR-based detection (1,2), several amplification methods have been invented. They include nucleic acid sequence-based amplification (NASBA) (3), self-sustained sequence replication (3SR) (4) and strand displacement amplification (SDA) (5,6). Each of these amplification methods has its own innovation to re-initiate new rounds of DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Strand-displacement reactions are known to permit DNA amplification in very high yields (Walker et al 1992;Lizardi et al 1998;Dean et al 2001). We have adapted the use of the strand-displacing polymerases of phage 29 and Bacillus stearothermophilus (Bst DNA polymerase large fragment, 5Ј → 3Ј exo ‫מ‬ ) for random-primed amplification of human genomic DNA.…”
mentioning
confidence: 99%
“…However, new PCR technologies, such as isothermal PCR, are of particularly practical use in the diagnosis of enteric fever, as these methods allow for the possibility of developing less-complicated and less-expensive machinery than is necessary for conventional PCR. Several isothermal PCR technologies have been developed (Gill & Ghaemi, 2008), including strand displacement amplification (SDA) (Walker et al, 1992), loop-mediated amplification (LAMP) (Notomi et al, 2000), and helicase-dependent amplification (HDA) (Vincent et al, 2004). Recently, Francois et al have examined the robustness of LAMP for bacterial diagnostic applications using S. Typhi as the target organism (Francois et al, 2011), and demonstrated that LAMP is more sensitive than conventional qPCR and is also a very robust, innovative and powerful molecular diagnostic method.…”
Section: Future Perspectivesmentioning
confidence: 99%